CURRENT DIAGNOSIS AND MANAGEMENT OF CROHN’S DISEASE: A LITERATURE-BASED REVIEW - Pambudi, Novanda Ayu Dila Putri; Siregar, Chivan Agustinus; Santoso, Arysatya Syandana Ararya; Sari, Padmi Kartika; Rachman, Amanda Azkiyah; Hudhori, Syalsa; Muharis, Nihal Ahmad (Mandala Of Health, 2025)
Crohn’s disease is a chronic inflammatory disorder of the gastrointestinal tract with increasing global incidence, shifting from a predominantly Western condition to a rising burden in Asia and other developing regions. Diagnosis requires a multimodal approach, integrating history, laboratory testing, endoscopy with validated activity scores, histopathology, and imaging such as magnetic resonance enterography or intestinal ultrasound. The 2024 ECCO guidelines emphasize fecal biomarkers like calprotectin as non-invasive monitoring tools within a treat-to-target strategy. Management includes pharmacological therapy (corticosteroids, immunomodulators, biologics, and novel small molecules), non-pharmacological measures (exclusive enteral nutrition, micronutrient supplementation, and diet modification), and surgery for refractory strictures, perforations, or complex fistulas. Beyond physical symptoms, Crohn’s disease carries a significant psychosocial burden, underscoring the need for nutritional and psychological support. Despite therapeutic advances, no curative treatment exists. Future research should focus on identifying more accurate biomarkers, improving accessibility to advanced therapies in low-resource settings, and exploring innovative approaches such as precision medicine, microbiota-targeted therapy, and genetic-based interventions.